2009
DOI: 10.1209/0295-5075/86/67003
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of oxygen isotope substitutions in the quasiparticle spectrum of Bi 2 Sr 2 CaCu 2 O 8+δ

Abstract: Abstract. -There is an ongoing debate about the nature of the bosonic excitations responsible for the quasiparticle self energy in high temperature superconductors -are they phonons or spin fluctuations? We present a careful analysis of the bosonic excitations as revealed by the 'kink' feature at 70 meV in angle resolved photoemission data using Eliashberg theory for a d-wave superconductor. Starting from the assumption that nodal quasiparticles are not coupled to the (π, π) magnetic resonance, the sharp struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Recent ARPES experiments along the nodal direction 16 found a shift in the 'boson kink' in the renormalized dispersion curves of Bi2212 upon oxygen isotope substitution. This was assigned by Schachinger et al 15 as a 10% phonon contribution to the electron-boson spectral density found in inversions 10 of ARPES data as reproduced in Fig. 1(d).…”
Section: Jiang and Carbottesupporting
confidence: 57%
See 1 more Smart Citation
“…Recent ARPES experiments along the nodal direction 16 found a shift in the 'boson kink' in the renormalized dispersion curves of Bi2212 upon oxygen isotope substitution. This was assigned by Schachinger et al 15 as a 10% phonon contribution to the electron-boson spectral density found in inversions 10 of ARPES data as reproduced in Fig. 1(d).…”
Section: Jiang and Carbottesupporting
confidence: 57%
“…For nodal ARPES there is no peak at ∼ 30 meV but one appears instead at much higher energy ∼ 65 meV. This higher energy has often been identified with coupling to oxygen phonons [4][5][6]15,16 and we will return to this issue later. Such a peak is not seen in our Raman spectra which indicates that such effects are mainly confined to the nodal direction and do not appear in averaged quantities such as B 1g and even B 2g Raman even though for this latter polarization the Raman vertex peaks in the nodal direction.…”
mentioning
confidence: 81%
“…A very detailed low-hν ARPES study found an isotope shift in the energy of the nodal kink [19], giving strong merit to the phonon scenario. One possible explanation for this conflict is that electron-phonon interactions might constitute a finite but relatively small contribution to the total self-energy [49]. Alternatively, the results may signal a role for coupling between spin and lattice degrees of freedom [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…An isotope effect in the dispersion of nodal QPs has been recently reported on optimally-doped Bi2212, by ARPES measurements [32]. These data have been carefully analyzed [33], demonstrating that the nodal isotope effect can be explained assuming that the QP-phonon coupling represents about 10% of the total contribution of other bosonic excitations. From Figure 3, we estimate that the contribution of SCP is less than 20% of the total bosonic function.…”
mentioning
confidence: 93%